Politik Pembangunan Organisasi Himpunan Keluarga Besar Mandailing “HIKMA” di Sumatera Utara - Burhanuddin Siregar; Heri Kusmanto; Warjio Warjio (Universitas Medan Area, 2020)
The purpose of this study is to identify forms of expression of social organization identity in development policy and political agendas; analyze the function and role of HIKMA as a political actor in development. This research use desciptive qualitative approach. The results showed that the activities and management practices in the social and political environment of the development of the HIKMA organization carried out contained the causality of the cultural and religious traditions of the Mandailing people. From the values and character of the Mandailing community, found a number of basic principles that reinforce the practice of local wisdom at the community level, namely the value of expediency, cohesiveness, kinship of the community members as well as the values of love and unity that are part of Mandailing's noble culture; and Islamic values. HIKMA has a strong connection with the traces of political development activities with the culture and traditions of the people of Mandailing in the past, which are recorded in symbolic expressions through actions, languages, and traditions in daily life. HIKMA and its relation to development politics, do not involve themselves in practical politics but critically encourage political struggles that are practical or oriented and collaborate on power to develop their regions. In this case the political struggle carried out by the political forces of HIKMA really put the interests of the Mandailing people in particular and the community at large. These cultural values are the basic spirit and purpose of the HIKMA struggle.